1998
DOI: 10.1046/j.1365-2346.1998.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal nerve blockade with a mixture of bupivacaine and phenol enhance the efficacy of intravenous patient-controlled analgesia in the control of post-cholecystectomy pain

Abstract: Prolonged nerve conduction blockade has been proposed to result from the summed effects of charged and neutral local anaesthetics. Thirty-seven patients were randomly allocated to receive intravenous patient-controlled analgesia alone or combined with intercostal blockade (T7-T11) with a mixture of 0.45% bupivacaine and 0.6% phenol for post-cholecystectomy analgesia. Adequacy of pain relief was measured by patient scores on a 10-cm visual analogue scale and by dose-demand ratio, amounts of loading dose and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Because the type of anesthetic procedure and the time of surgery in both investigated groups were identical, we concluded that the pain reduction in our series was mainly attributable to INB. Our findings differ from those reported earlier for open cholecystectomies [9]. Thus, it might be assumed that the postoperative pain mechanisms after LC and open cholecystectomy are different [6,8,17].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Because the type of anesthetic procedure and the time of surgery in both investigated groups were identical, we concluded that the pain reduction in our series was mainly attributable to INB. Our findings differ from those reported earlier for open cholecystectomies [9]. Thus, it might be assumed that the postoperative pain mechanisms after LC and open cholecystectomy are different [6,8,17].…”
Section: Discussioncontrasting
confidence: 99%
“…Intercostals neural blockade is used in various conditions of acute and chronic pain affecting the thorax and upper abdomen (e.g., postoperative analgesia after thoracotomies [15] and open cholecystectomies). It has been recommended as a complement to systemic morphine injections in the latter [9]. Its advantages are superior analgesia, opioid sparing, improved pulmonary mechanics, reduced central nervous system depression, and avoidance of urinary retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that continuous intercostal nerve blocks lead to better pain control in these patients. 158 For patients undergoing laparoscopic cholecystectomy, pain severity 159 and postoperative morphine consumption 160 were significantly reduced by intercostal nerve blockade. In addition, the duration of the need for patient-controlled analgesia was significantly decreased.…”
Section: Effectiveness One Of the Most Important Indications Formentioning
confidence: 99%
“…In addition, the duration of the need for patient-controlled analgesia was significantly decreased. 160 With open cholecystectomy, intraoperative inhalation anaesthetic use was significantly reduced by the use of intercostal nerve blocks. 161 In cardiac surgery 162 163 and after major lung resections, 164 pain scores were significantly improved with a lower systemic analgesic requirement when compared with placebo.…”
Section: Effectiveness One Of the Most Important Indications Formentioning
confidence: 99%